Review of Advanced Water Treatment for Removal of Nanoplastic Pollution - Putri, Widia; Komala, Puti Sri (CIVED, 2023)
Drinking water is a very important basic need for humans. One of the detected drinking water pollution that greatly affects the quality is the content of nanoplastics. In aquatic ecosystems, nanoplastics are materials that cannot be decomposed. Through this brief review, the efficiency of removing nanoplastics using various water treatment methods will be reviewed. Some of the treatment methods reviewed are nanoplastic removal using filtration, adsorption, coagulant and flocculant addition, and CFS (Coagulation/Flocculation Sedimentation). The research method used is a literature review related to drinking water treatment to eliminate pollution by nanoplastics. The conclusion from the literature review is that the process of treating drinking water by filtration with the addition of coagulants is the most efficient treatment for removing pollution by nanoplastics, reaching 99.9%.